Empathy-In-Teaching as a Multidimensional Disposition in Counselor Education - Eric R Baltrinic; Melissa Luke (Teaching and Supervision in Counseling, 2022)
Empathy is a disposition noted among established teaching competencies in counselor education. However, current descriptions of empathy are unidimensional and lack an operational definition for evaluating teaching dispositions. The term empathy-in-teaching is a multidimensional concept suitable for expanding our current understanding of empathy within the current teaching dispositions in counselor education. Implications for application of the concept of empathy-in-teaching within the current teaching dispositions and future research suggestions are offered.
Keywords: empathy; empathy-in-teaching; teaching dispositions; counselor education